Development of Classroom Action Research Modules in Christian Education Subjects - Lustani Samosir; Johari Manik; Dian Purba; Endang Juliati Br. Manullang (Budapest International Research and Critics University, 2022)
This research aims to develop a classroom action research module equipped with examples of classroom action research on Christian education. This is motivated by the importance of teachers doing classroom action research to improve learning poses and improve learning outcomes in accordance with the goals of the field of study. From the results of the analysis of the needs of teachers for the importance of knowledge of implementing classroom action research, information was obtained that from 297 teachers of Christian education, 98% stated that it was very important to do classroom action research in the field of Christian education, but did not understand how to do it, it was needed modules as a guide to carrying out classroom action research and examples of classroom action research in the implementation of Christian education. This research uses a 4D model development approach with stages of define, design, develop and disseminate. The results of the research are in the form of classroom action research modules equipped with examples in the learning of Christian Education class VII with the title